Religion In Antebellum Kentucky - Boles, John B. (Book collections on Project MUSE., 2015)
Religion permeated the day-to-day life of antebellum Kentucky. This engaging account of Kentucky's various Christian denominations, first published as part of the Kentucky Bicentennial Bookshelf, traces the history of the Great Revival of 1800--1805, the subsequent schism in Protestant ranks, the rise of Catholicism, the development of a distinctive black Christianity, and the growth of a Christian antislavery tradition. Paying special attention to the role of religion in the everyday life of early Kentuckians and their heritage, John B. Boles provides a concise yet enlightening introduction to.